Production of Versatile Peroxidase from Pleurotus Eryngii by Solid-State Fermentation Using Agricultural Residues and Evaluation of Its Catalytic Properties - Contreras-Villacura, E; Sepulveda-Cuevas, L (Taylor and Francis Inc., 2016)
Interest in production of ligninolytic enzymes has been growing over recent years for their use in various applications such as recalcitrant pollutants bioremediation; specifically, versatile peroxidase (VP) presents a great potential due to its catalytic versatility. The proper selection of the fermentation mode and the culture medium should be an imperative to ensure a successful production by an economic and available medium that favors the process viability. VP was produced by solid-state fermentation (SSF) of Pleurotus eryngii, using the agricultural residue banana peel as growth medium; an enzymatic activity of 10,800 U L-1 (36 U g-1 of substrate) was detected after 18 days, whereas only 1800 U L-1 was reached by conventional submerged fermentation (SF) with glucose-based medium. The kinetic parameters were determined by evaluating the H2O2 and Mn2+ concentration effects on the Mn3+-tartrate complex formation. The results indicated that although the H2O2 inhibitory effect was observed for the enzyme produced by both media, the reaction rates for VP obtained by SSF were less impacted. This outcome suggests the presence of substances released from banana peel during the fermentation, which might exhibit a protective effect resulting in an improved kinetic behavior of the enzyme. Copyright © Taylor & Francis Group, LLC 2016.